"Mãos que afagam e afastam": redes sociais do cuidado às pessoas com hanseníase - Pereira, Thayza Miranda (Universidade Estadual do Ceará, 2025)
Leprosy is a chronic and neglected disease with a high incapacitating power, which is attributed to a late diagnosis and social stigma about becoming ill. Social networks are relationships that connect different people, groups or institutions, that own bigger or smaller cohesion, interactivity, sustainability, duration, among other attributes. The objective of this study is getting to know the social networks of the people who are affected by leprosy from the perspective of care. The approach of the study is quantitative-qualitative anchored in the Social Network Analysis framework and the Bourdieu nuclear concepts. Data collection was held in two territorial scopes of the Family Health Strategy Program with high endemicity for leprosy, in the municipality of Sobral-Ceará, from July to August 2017, through documental analysis (information systems and territorial reports of the boroughs Sumaré and Padre Palhano) and semi-structured interviews held with 17 people affected by leprosy. In order to get to know the territorial care social networks, the Ucinet © and NetDraw © software were utilized and quantitative representation through graphs was obtained. The statements obtained in the interviews subsidized the qualitative dimension in the data analysis through narratives. This study was approved by the Research Ethics Committee of the State University of Ceará, ethical approval number 2,100,093. The social networks of people affected by leprosy are egocentric, with a focus on the family (primary network) and healthcare practioners and health services (secondary network). Regarding to the degree of mediation among subjects and healthcare practioners, the network depicted the importance of the bondage established by the community health agent in the process of listening and caring as well as the relevance of the cultural capital related to the reference service in leprosy. From the social agent narratives, three categories emerged: Institutional network: surveillance of visible bodies; Family network as support for coping with the disease; Produced senses: hands that caress and push away. In the narratives, it has been noticed the importance of family and friendship bonds as a way of supporting and being affectionate during the illness; the long await to find out the disease and the onset of the treatment; the search for information about the disease on the internet; the physical incapacities and the reactional episodes as maintainer of the social stigma, thus setting up a surveillance of the scars on the body. The analysis of these categories has unfolded the imminent need to rethink the context of the social health practice of the person with leprosy, aiming at overcoming normative models in the process of care by the health services, considering the sociocultural and political dimension in the production of knowledge incorporated and established in the subjects' daily life, thus making the social network a possibility of construction, interaction and understanding of leprosy care.